EuroEVA: results from whole genome sequencing - Pechirra, Pedro (2019)
In the 2016/17 season, the Portuguese NIC has used NGS for genetic characterization of influenza viruses detected in samples from EuroEVA (the Portuguese component of I-MOVE). This study aims to analyse the whole genome of influenza viruses from vaccinated and unvaccinated cases and reveal possible viral genetic causes assigned to the vaccine failure. Nasopharyngeal swabs were collected from patients with influenza-like illness selected in primary care settings. Viral RNA was extracted directly from biological samples and after multiplex PCR amplification, the whole genome was sequenced for 84 influenza A(H3) viruses by deep sequencing on a MiSeq platform. All influenza A(H3) viruses clustered in 2 genetic subgroups: 3C.2a and 3C.2a1 (predominant). Sixteen viruses (19%) were from vaccinated individuals (12% in 3C.2a and 23% in 3C.2a1 groups). Only 7 cases of vaccine failure presented amino acid substitutions, not found among unvaccinated cases. A slightly higher dN/dS ratio of HA gene was detected among vaccinated cases. Only 5 cases of vaccine failure harbored nucleotide variants on their genome (from 7 detected sequence variants, only one has changed the amino acid). The proportion of vaccinated cases was higher in new 3C.2a1 group than in 3C.2a. Few amino acid substitutions found only in vaccinated cases occurred sporadically, as well as the nucleotide variants, most of them are synonymous substitutions. Viral HAs from vaccinated cases seem to present a slightly higher dN/dS ratio than from unvaccinated cases.